Lexis in political ideas on Twitter - Ramanathan, Renugah; Tan, Bee Hoon; Paramasivam, Shamala (Australian International Academic Centre, 2017)
Ideologies in political discourse have been keen research topics as they provide various views of an issue or event. The prominent aspect of ideology is that it attempts to bridge the political activism to the social world that reflects the authenticity of political figures. This study aims to compare the ideological notions in the political tweets of Prime Minister Najib Tun Razak (henceforth, Najib) and Prime Minister Narendra Modi (henceforth, Modi) during the election campaigns. The discourse between both the political premiers are compared in relation to their active participation on Twitter in Asia. Data were collected over a period of 3 months during the election campaigns of both the countries which were from February to April 2013 in Malaysia and January to March 2014 in India. The study follows the qualitative research design by employing Fairclough’s three dimensional model in analyzing the lexical choices and the formation of ideas. The presence of various ideologies in the tweets portray the consensual power of the political leaders as the citizens accepts the former’s principles, ideologies and moral values. Hence, this study is significant because the study increases political awareness among citizens and provides insights on how language is employed by both leaders from different political coalition. Besides, this study produces knowledge that helps society to understand how 140 character can be a powerful tool in disseminating ideas during national elections and making election a success.